Global Trend in the Research and Development of Acupuncture Treatment on Parkinson's Disease From 2000 to 2021: A Bibliometric Analysis - Li, Xiaoping; Wei, Wan; Wang, Yuan; Wang, Qiang; Liu, Zhibin (Frontiers in Neurology, 2022)
Background Acupuncture has been widely used in the treatment of patients with Parkinson's disease (PD) in the world. Despite we have an in-depth understanding of acupuncture in this field over the past years, there is no available literature on bibliometric analysis on the development of acupuncture on PD. This study was designed to explore the global trend in the research of acupuncture on PD in the recent 20 years by the software CiteSpace (5.8.R3) and VOSviewer (1.6.14). Methods Publications regarding acupuncture therapy for PD from 2000 to 2021 were retrieved from the Web of Science Core Collection database. CiteSpace and VOSviewer were used to analyze the number of publications, the contribution of countries, institutions, journals, authors, references, and keywords. Results A total of 217 studies were extracted from the database. The outputs of the publications in this field showed an upward trend during the past two decades. The country and institutions with the most publications in this field are China, South Korea, and the USA. They were the main contributors to the research. Kyung Hee University and Capital Medical University were the two most productive organizations. Hi-Joon Park had made the greatest contributions to the field. Evidence-based Complementary and Alternative Medicine was the most popular journals in this field. “Electroacupuncture” and “Bee venom acupuncture” were emerging research hotspots. Conclusion The research on acupuncture on PD is potential. Authors from different countries/regions and organizations need to remove the language and academic barriers to enhance global cooperation and communications. Scholars in this field need to publish their research findings in high-quality journals to gain more attention worldwide. This study indicated that the mechanism leading to the non-motor symptoms of PD, the establishment of appropriate models that fully reflects the non-motor features of human PD, and the efficacy and safety of promising therapies for patients with PD will remain research frontiers in the future.